2021
DOI: 10.1007/978-3-030-68211-8_22
|View full text |Cite
|
Sign up to set email alerts
|

APX-Hardness and Approximation for the k-Burning Number Problem

Abstract: Consider an information diffusion process on a graph G that starts with k > 0 burnt vertices, and at each subsequent step, burns the neighbors of the currently burnt vertices, as well as k other unburnt vertices. The k-burning number of G is the minimum number of steps b k (G) such that all the vertices can be burned within b k (G) steps. Note that the last step may have smaller than k unburnt vertices available, where all of them are burned. The 1-burning number coincides with the well-known burning number pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 20 publications
(31 reference statements)
0
8
0
Order By: Relevance
“…García-Díaz et al [10] have given a (3 − 2/b)-approximation algorithm where b is the burning number of the input graph. Mondal et al [17] have shown the graph burning problem to be APX-hard, even in a generalized setting where k = O(1) vertices can be chosen to initiate the fire at each step. They gave a 3-approximation algorithm for this generalized version [17].…”
Section: Related Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…García-Díaz et al [10] have given a (3 − 2/b)-approximation algorithm where b is the burning number of the input graph. Mondal et al [17] have shown the graph burning problem to be APX-hard, even in a generalized setting where k = O(1) vertices can be chosen to initiate the fire at each step. They gave a 3-approximation algorithm for this generalized version [17].…”
Section: Related Resultsmentioning
confidence: 99%
“…Mondal et al [17] have shown the graph burning problem to be APX-hard, even in a generalized setting where k = O(1) vertices can be chosen to initiate the fire at each step. They gave a 3-approximation algorithm for this generalized version [17]. Since the introduction of the graph burning problem [5], a rich body of literature examines the upper and lower bound on the graph burning number for various classes of graphs [20,14,8] as well as the parameterized complexity of computing the burning number [13].…”
Section: Related Resultsmentioning
confidence: 99%
“…A graph decision problem is APX-hard if there is a polynomial time approximation scheme reduction from every problem in APX to that problem. In [33], it was proven that the Graph Burning problem is APX-hard, answering a question from [8]. It was also proven in [33] that even if the burning sources are given as an input, computing a burning sequence itself is NP-hard.…”
Section: Complexity Of Graph Burningmentioning
confidence: 99%
“…In [33], it was proven that the Graph Burning problem is APX-hard, answering a question from [8]. It was also proven in [33] that even if the burning sources are given as an input, computing a burning sequence itself is NP-hard.…”
Section: Complexity Of Graph Burningmentioning
confidence: 99%
See 1 more Smart Citation